Intergenerational health mobility in the US - Timothy Halliday; Bhashkar Mazumder; Ashley Wong (Federal Reserve Bank of Chicago, 2018)
Studies of intergenerational mobility have largely ignored health despite the central importance of health to welfare. We present the first estimates of intergenerational health mobility in the US by using repeated measures of self-reported health status (SRH) during adulthood from the PSID. Our main finding is that there is substantially greater health mobility than income mobility in the US. A possible explanation is that social institutions and policies are more effective at disrupting intergenerational health transmission than income transmission. We further show that health and income each capture a distinct dimension of social mobility. We also characterize heterogeneity in health mobility by child gender, parent gender, race, education, geography and health insurance coverage in childhood. We find some important differences in the patterns of health mobility compared with income mobility and also find some evidence that there has been a notable decline in health mobility for more recent cohorts. We use a rich set of background characteristics to highlight potential mechanisms leading to intergenerational health persistence.
Keywords: 330; Intergenerationenmobilität; Gesundheit; Schätzung; USA